2016
DOI: 10.1002/jcb.25579
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmotic Stress Induces Tau Proteolysis by Caspase‐3 Activation in SH‐SY5Y Cells

Abstract: Tau is a microtubule-associated protein implicated in the pathogenesis of Alzheimer's disease and other related tauopathies. In this subset of neurodegenerative disorders, Tau auto-assembles into insoluble fibrils that accumulate in neurons as paired helical filaments (PHFs), promoting cellular dysfunction and cytotoxic effects. Growing evidence suggests that abnormal post-translational regulation, mainly hyperphosphorylation and aberrant cleavage, drives Tau to this pathological state. In this work we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Dehydration naturally occurs in humans and other animals for a number of reasons, including in the context of ageing and neurodegenerative diseases [4, 6, 7]. Of note, hyperosmotic stress clearly activates autophagy in nerve cells as previously reported in several studies using other types of cells [912].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Dehydration naturally occurs in humans and other animals for a number of reasons, including in the context of ageing and neurodegenerative diseases [4, 6, 7]. Of note, hyperosmotic stress clearly activates autophagy in nerve cells as previously reported in several studies using other types of cells [912].…”
Section: Discussionmentioning
confidence: 82%
“…Alzheimer's disease patients present an impaired response to fluid restriction, even in a mild overnight fluid restriction paradigm [5]. Increased tau phosphorylation and production of beta amyloid precursor proteins were also found in neuronal cells exposed to hyperosmotic stress, leading to altered cleavage of amyloid precursor protein, increasing beta amyloid peptides [6, 7]. Despite the enormous importance of understanding the homeostatic mechanisms underlying the response of nerve cells to osmotic stress, this topic has been underrepresented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the polyol pathway is necessary for ChREBP nuclear localization in hepatocytes and glucose tolerance in mice, and long-term uptake of sorbitol could induce a significant change in the composition of the gut microbiome [38]. The further work showed that sorbitol could induce an upregulation of Aquaporins 7 expression in a time-dependent manner [39] and apoptosis [40,41]. What is more, sorbitol was found to be able to relay gutfat body immunological communication (GFIC) by activation of metalloprotease 2, which further cleaved PGRP-LC to The classical second messenger cAMP pathway has been confirmed to be essential for a variety of physiological functions, including mitochondrial biology, lipid metabolism, ischemia, and inflammation [42].…”
Section: Discussionmentioning
confidence: 99%
“…References report recent usage of each stressor to human SH-SY5Y neuroblastoma cells Stressor Effect Acute Treatment Chronic Treatment References Serum Deprivation (SD) Lack of growth factors; Reduced nutrition / 1%. 72 h [ 32 ] Sodium Arsenite (Ars) Oxidative stress; Mitochondrial disruption 0.5 mM 1 h 20 µM 72 h [ 33 ] D-Sorbitol (Sorb) Hyperosmotic stress; Small molecules leakage 1.2 M 2 h 120 mM 72 h [ 34 ] Paraquat (PQ) Oxydative stress; ROS production 2 mM O.N 0.2 mM 72 h [ 35 ] …”
Section: Methodsmentioning
confidence: 99%